Association of the cytochrome P450 and arylamine N-acetyltransferase gene polymorphisms with the incidence of head and neck cancer in Polish population - Monika Gogolewska; Jacek Kabziński; Ireneusz Majsterek (International Journal of Occupational Medicine and Environmental Health, 2023)
Objectives Head and neck cancer (HNC) is one of the most common cancers. Most exogenous HNC is head and neck squamous cell carcinomas. Scientists are striving to develop diagnostic tests that will allow the prognosis of HNC. The aim of the study was to determine the risk of HNC. The research concerned changes caused by polymorphisms in genes encoding proteins responsible for the metabolism of xenobiotics.